2011
DOI: 10.3138/cmlr.67.4.536
|View full text |Cite
|
Sign up to set email alerts
|

Well, Now, Okey Dokey: English Discourse Markers in Spanish-Language Medical Consultations

Abstract: The purpose of this paper is to examine use of English discourse markers in otherwise Spanish language consultations. Data is derived from an audio-recorded corpus of Spanish language consultations that took place in a small community clinic in the United States as well as postconsultation interviews with patients and providers. Through quantification of the use of discourse makers in the corpus and discourse analysis of transcripts, we demonstrate that English-speaking dominant medical providers use English d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…As can be clearly seen, the most frequent EDMs are not the same among learners from different world countries. Unlike Spanish subjects, for example, who used the EDMs "so", "but" and "now" more than any other EDMs (Torres & Potowski, 2008;Vickers & Goble, 2011), "and", "also", and "besides" found to be the most frequent EDMs in the talk of Saudi subjects and this can be clearly seen in Tables 1,2, 3 and Figure 1. Also, Chinese subjects used EDMs "and", "also" and "but" more than the EDMs "however", because" and "so" (Wang, 2009;Zhung, 2012).…”
Section: Edms Frequency Among Native and Non-native Learnersmentioning
confidence: 84%
See 1 more Smart Citation
“…As can be clearly seen, the most frequent EDMs are not the same among learners from different world countries. Unlike Spanish subjects, for example, who used the EDMs "so", "but" and "now" more than any other EDMs (Torres & Potowski, 2008;Vickers & Goble, 2011), "and", "also", and "besides" found to be the most frequent EDMs in the talk of Saudi subjects and this can be clearly seen in Tables 1,2, 3 and Figure 1. Also, Chinese subjects used EDMs "and", "also" and "but" more than the EDMs "however", because" and "so" (Wang, 2009;Zhung, 2012).…”
Section: Edms Frequency Among Native and Non-native Learnersmentioning
confidence: 84%
“…Others preferred examining the use of EDMs outside the pedagogical frame. Vickers & Goble (2011) investigated the use of some EDMs including: "Well" and "Now" among Spanish speakers working in the field of medicine. The two researchers show that out of 915 English words, 317 tokens EDMs were used.…”
Section: Introductionmentioning
confidence: 99%
“…This contradicts Turner"s views (1999) he, argues that "Okay" and "Alright" have a distinctive usage. According to, Turner"s argument, "Alright" has a major mark in shifting topics or moving to another activity, whereas "Okay" marks delicate shifts, with more focus within the unchanged topic (cited in Vickers & Goble, 2011). Recently, a study conducted by Walsh & O"Keeffe (2010) reveals that the response token "Okay" is found more profoundly at the beginning of interactions with other cluster responses.…”
Section: Discussionmentioning
confidence: 99%
“…Given that Spanish was the primary language of the task, these ratios aim to quantify the extent to which English is used by participants, whether it be lone word or multi-word insertions. Other authors have used similar measures: for example, Vickers and Goble (2011) calculated the percentage of English words in Spanish-language medical consultations; Raichlan, Walters and Altman (2018) used a ratio of utterances that contained codeswitches out of the total number of utterances in Russian–Hebrew bilingual children's speech; and Torres and Potowski (2016) calculated the total number of English words compared to total number of words uttered in Spanish-language oral interviews. Since our goal was primarily to compare self-reported to actual codeswitching practices, our measures differ from other measures of codeswitching, such as burstiness (which would measure codeswitching density) and M-Index (which would classify a corpus as relatively monolingual or bilingual) (Guzman, Bullock & Toribio, 2017).…”
Section: Methodsmentioning
confidence: 99%